Peningkatan Nilai Tambah Produksi Tahu Bagi Kelompok Produsen Tahu di Sokaraja Tengah Kecamatan Sokaraja Kabupaten Banyumas - rakhmawati, desty (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2019)
Sokaraja is one of the sub-districts included in the Banyumas Regency, led by a Regent named Ir. Achmad Husein and his deputy named Dr. Budhi Setiawan. Sokaraja aside from being a center for learning for students centered on the Kauman Mosque in Central Sokaraja, Sokaraja is also the birthplace of fighters such as R.Separdjo Roestam, Gatot Soebroto, and other high-ranking officials in Indonesia. Sokaraja is very famous for Soto Sokaraja, Batik Sokaraja and Getuk goreng, so most of the residents of Sokaraja Village are sellers of soto, batik makers and getuk goreng products. In addition to earning a living as a seller of soto, batik maker and getuk goring production, but many also earn a living as producers of tofu. Tofu is a food product made from the clumping of soy protein. Tofu production is still not widely known by the wider community, compared to the production of fried getuk, batik and soto sokaraja which are already very well known to the wider community.